2007
DOI: 10.1074/jbc.m702854200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Acetyl-CoA Carboxylase α and Fatty Acid Synthase by Human Epidermal Growth Factor Receptor 2 at the Translational Level in Breast Cancer Cells

Abstract: Expression of the HER2 oncogene is increased in ϳ30% of human breast carcinomas and is closely correlated with the expression of fatty acid synthase (FASN). In the present study, we determined the mechanism by which FASN and acetyl-CoA carboxylase ␣ (ACC␣) could be induced by HER2 overexpression. SK-BR-3 and BT-474 cells, breast cancer cells that overexpress HER2, expressed higher levels of FASN and ACC␣ compared with MCF-7 and MDA-MB-231 breast cancer cells in which HER2 expression is low. The induction of FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 53 publications
7
158
1
1
Order By: Relevance
“…Indeed, it has been previously shown that the overexpression of FASN is most intense in carcinomas with higher risk of both disease recurrence and death, and steroid hormones, growth factors (EGFR, ERBB2), and the phosphatidylinositol-3 kinase (PI3K)-Akt signaling pathway regulate FASN expression (1,(27)(28)(29). There are also several publications showing the interconnection of FASN activity and HER2 signaling pathway (27,30,31). In the lipidomic and immunohistochemical analyses, we did not find major associations to the HER2 status, and thus our results challenge the earlier conceptions that HER2 signaling would have a major effect on the lipid metabolism (27).…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, it has been previously shown that the overexpression of FASN is most intense in carcinomas with higher risk of both disease recurrence and death, and steroid hormones, growth factors (EGFR, ERBB2), and the phosphatidylinositol-3 kinase (PI3K)-Akt signaling pathway regulate FASN expression (1,(27)(28)(29). There are also several publications showing the interconnection of FASN activity and HER2 signaling pathway (27,30,31). In the lipidomic and immunohistochemical analyses, we did not find major associations to the HER2 status, and thus our results challenge the earlier conceptions that HER2 signaling would have a major effect on the lipid metabolism (27).…”
Section: Discussioncontrasting
confidence: 57%
“…The expression level of FASN is relatively low in the majority of normal tissues, however; increased expression of FASN has been identified in human breast cancer cells, particularly in SK-BR-3 cells (37). According to previous studies on tumor proliferation, FASN may contribute to the generation of tumor cell membranes (43).…”
Section: Discussionmentioning
confidence: 99%
“…Graner et al showed that the isopeptidase USP2a (ubiquitin-specific protease-2a) interacts with and stabilises FASN protein in prostate cancer (Graner et al, 2004). In breast cancer BT-474 cells that overexpress HER2, the expression of FASN and ACC are not mediated by SREBP-1, but by a mammalian target of rapamycin (mTOR)-dependent selective translational induction (Yoon et al, 2007). A significant copy number gain of FASN gene is also observed in prostate adenocarcinoma (Shah et al, 2006).…”
Section: Regulation Of Fasn and De Novo Fatty-acid Synthesis Pathway mentioning
confidence: 95%